Corporate governance, firm performance and Chinese state enterprise reform / Zhang Cheng - Zhang, Cheng (2017)
While corporate governance continues to play an important role in economic development, corporate governance issues are more complex in transition economies than in the developed market economies. Consequently, policy makers in transition economies have been busy attempting to establish a sound corporate governance system in their countries. This study uses China as a laboratory to explore corporate governance issues, as China is not only the most populous economy in the world, it is also undergoing transition from a socialist to a market economy since 1978. The need for strengthening corporate governance in the country has become all the more pressing as rapid economic growth has transformed the economy since especially the 1990s. China experienced a watershed in corporate governance when the split-share structure reform was introduced. Hence, we analyse in this thesis the impact of this reform on board composition, firm performance, and firm risk over the period before and after the introduction of the reform. Firms are classified by ownership into central government, local government, state owned enterprise (SOE) and privately controlled firms based on ultimate controlling shareholders. The study deploys static and dynamic panel data estimation methods to examine the determinants of corporate board composition, relationships between corporate governance mechanisms and firm performance, and the relationships between corporate governance mechanisms and firm risk. The results show that Chinese corporate board composition is jointly determined by the scope of operation (resource dependent theory), monitoring (agency theory), bargaining (power theory), other governance mechanisms (stakeholder theory) and regulations (institution theory). The government was the most important player in constituting board composition before the split-share structure reform was introduced, but independent directors became more important than other governance mechanisms after that. Private firms and SOEs are more concerned about cost than other factors when adding independent directors. Also, corporate board exerts a positive influence on firm performance once the share of independent directors reached 30 percent. Although the supervisory board can make up for the inadequate number of independent directors, its role became insignificant after the reform. Central government controlled firms show outstanding accounting and market performance. While increasing corporate board size reduced firm risk, its independence increased firm risk. State ownership and ownership concentration increased firm risk after reforms. Overall, the findings confirm the applicability of corporate governance theories to China. Other transition economies can draw lessons from the institutional change that have played a significant role in the evolving Chinese corporate governance system. Government-controlled firms should be more market-oriented so as to reduce the unnecessary influence of political power on firms activities. It also sheds light on the partial privatization approach that may work for other transition economies.